2018
DOI: 10.1136/heartjnl-2017-312409
|View full text |Cite
|
Sign up to set email alerts
|

Interphysician agreement on subclassification of myocardial infarction

Abstract: ObjectiveThe universal definition of myocardial infarction (MI) differentiates MI due to oxygen supply/demand mismatch (type 2) from MI due to plaque rupture (type 1) as well as from myocardial injuries of non-ischaemic or multifactorial nature. The purpose of this study was to investigate how often physicians agree in this classification and what factors lead to agreement or disagreement.MethodsA total of 1328 patients diagnosed with MI at eight different Swedish hospitals 2011 were included. All patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 25 publications
2
18
0
3
Order By: Relevance
“…Previous studies examining the incidence of T2MI have shown wide incidence rates, partly explained by differences in diagnosis definitions, differences in cTn assays and cutoff values used, and study populations. 6 Our study, consistent with the findings from Gard et al, 16 shows that agreement rates for T2MI following UDMI diagnostic criteria are at the most fair-to-moderate. Our current study elaborates on these challenges by showing how the existing UDMI diagnostic criteria and the interpretation of symptoms, a subjective criterion, may also influence the incidence of T2MI in both clinical practice and research studies.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Previous studies examining the incidence of T2MI have shown wide incidence rates, partly explained by differences in diagnosis definitions, differences in cTn assays and cutoff values used, and study populations. 6 Our study, consistent with the findings from Gard et al, 16 shows that agreement rates for T2MI following UDMI diagnostic criteria are at the most fair-to-moderate. Our current study elaborates on these challenges by showing how the existing UDMI diagnostic criteria and the interpretation of symptoms, a subjective criterion, may also influence the incidence of T2MI in both clinical practice and research studies.…”
Section: Discussionsupporting
confidence: 92%
“…[3][4][5] Much debate exists surrounding how to diagnose T2MI, with a wide range in incident rates observed across studies, partly due to ambiguity and variation in how the diagnosis is established. [5][6][7][8][9][10][11][12][13][14][15][16] Challenges persist regarding its diagnosis in routine clinical practice and its adjudication in research studies. 6 Moreover, various studies have suggested that long-term outcomes between T2MI and myocardial injury (INJ) are similar.…”
Section: Introductionmentioning
confidence: 99%
“…Among the total number of 772 included MI patients in the present study, 6.2% were reported as type 2 MI compared with a true prevalence of 12%. In addition, the prevalence of type 2 MI among MI patients not registered in SWEDEHEART was 28% in 2011 [3], indicating that patients with type 2 MI are less often reported in the registry. Further, type 2 MI patients, compared with type 1 MI patients, are more often treated outside the cardiology department [3,11] which likely entails a certain risk of not getting a MI diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of conditions causing the ischemic imbalance in type 2 MI are tachycardia, anemia, shock and respiratory failure [2]. It is challenging to distinguish type 2 MI from type 1 MI and especially from myocardial injuries commonly occurring in patients with conditions such as heart failure, sepsis, renal failure and stroke [3].…”
Section: Introductionmentioning
confidence: 99%
“…Although the categorisation of patients was meticulously done, it might have been advantageous to enrol patients prospectively by repeating hs-cTnT measurements several weeks apart. There may have been misclassification of exposure mainly for the groups of acute non-ischaemic myocardial injury, T1MI and T2MI, which have been found difficult to distinguish previously 27. In addition, apart from patients with T1MI, coronary angiographies were rarely done in the other categories of myocardial injury.…”
Section: Limitationsmentioning
confidence: 99%